Handbook of Resistance Tactics Against Evictions. Collection of Tactics from Housing Justice and Anti-Racist Movements in Romania, Hungary, Serbia, Germany, Portugal and Spain - Ugron Nóra (Editura Fundaţiei Desire, 2026)
The practice of forced evictions should be abolished worldwide. Yet, evictions that leave both adults and children on the streets or in temporary shelters without adequate alternative housing make for an unjust reality that we are faced with every year. A vital question is left for the housing movement: what tactics should we use to show resistance to evictions and solidarity with those affected?
The goal of this publication is to be a manual, a toolbox that brings together tactics, methods, case studies, and various insights that work in
very different contexts. The chapters vary substantively in terms of format, style, and length. This reflects the fact that each eviction has a specific character, grounded in the local context. Therefore, it requires diverse and well-thought tactics, tailored to each situation. Nevertheless, there are recurring patterns both in the authorities’ and evictors’ methods, as well as in the possible methods for resistance. As such, the goal of this publication is to deepen our understanding of these tendencies and particularities.
Table of contents
Introduction: The Need for Strong Anti-Eviction Networks
by Nóra Ugron (Social Housing NOW! / Căși Sociale ACUM!, Cluj-Napoca, Romania), p. 7
Anti-Eviction Activism: Căși Sociale ACUM!, from Politics to Tactics and Back
by Enikő Vincze and Linda Greta Zsiga (Social Housing NOW!, Cluj-Napoca, Romania), p. 11
The Ethics of Solidarity and the Representation of Evictions. A Guide for How to Ethically Portray Evictions
by Veda Popovici (Common Front for Housing Rights / FCDL - Frontul Comun pentru Dreptul la Locuire, Bucharest, Romania), p. 27
Everyday Struggles for the Right to the City
by Tania Strizu (Right to the City / Dreptul la Oraș, Timișoara, Romania), p. 35
Housing and Evictions from an Intersectional Perspective
by Anca Georgiana Nica and Magdalena Roxana Oprea (E-Romnja, Bucharest, Romania), p. 39
Anti-Racist Juridical Views on Housing Justice Activism – The Strategies of RomaJust
by Eugen Ghiță (RomaJust) and Corina Andreea Preda (Romania), p. 47
On Resisting Evictions: The Anti-Eviction Emergency Service and the Use of Civil Disobedience
by Bálint Misetics (The City is for All / A Város Mindenkié, Budapest, Hungary), p. 53
The importance of tactics, knowledge and partnerships in preventing evictions
by Ivana Anđelković and Ivan Velisavljević (The Roof / Združena akcija 'Krov nad glavom', Belgrade, Serbia), p. 61
At the Origins of the Housing Movement in Portugal - The Struggle Against the Demolition of Self-built Neighborhoods
by Carlotta Monini (Habita 65, Lisabona, Portugalia), p. 67
Every Eviction is One Too Many!
by Bündnis Zwangsräumung Verhindern Berlin / Coalition Against Evictions Berlin (Berlin, Germania), p. 79
Don't Panic, Organize! Fighting for Housing Rights in Barcelona
by Sindicat d'Habitatge de Vallcarca The Housing Union of Vallcarca (Barcelona, Spania), p. 85